2009
DOI: 10.1002/clc.4960121317
|View full text |Cite
|
Sign up to set email alerts
|

Current aspects of high blood pressure research in Africa

Abstract: Hypertension in Africa represents a challenge and an opportunity. As the two epidemics of infection and malnutrition are increasingly brought under control, increasing morbidity and mortality from hypertension have been documented and offer a challenge for prevention. Heterogeneity within and between African populations offers opportunities for detecting clues to the etiology and pathogenesis of hypertension. For example, populations in urban areas have already shown a greater prevalence of obesity, hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This estimate is relatively comparable with the estimates reported for sub-Saharan Africa between 1981 and 2008 by Danaei et al [57], with an overall mean SBP ranging from 129.2 to 132.7 mmHg and 132.6 and 134.8 mmHg among men and women, respectively. This may broadly reflect an increasing overall mean blood pressure and a rising prevalence of hypertension in the country when compared to other world regions [58]. From the pooled crude prevalence rates, we observed that the prevalence of hypertension was higher among the urban dwellers than that observed among the rural dwellers (31 versus 26%).…”
Section: Discussionmentioning
confidence: 89%
“…This estimate is relatively comparable with the estimates reported for sub-Saharan Africa between 1981 and 2008 by Danaei et al [57], with an overall mean SBP ranging from 129.2 to 132.7 mmHg and 132.6 and 134.8 mmHg among men and women, respectively. This may broadly reflect an increasing overall mean blood pressure and a rising prevalence of hypertension in the country when compared to other world regions [58]. From the pooled crude prevalence rates, we observed that the prevalence of hypertension was higher among the urban dwellers than that observed among the rural dwellers (31 versus 26%).…”
Section: Discussionmentioning
confidence: 89%